The expected impact of IFRS 16 on retail companies - Borges, Samuel Luiz Dias (2019)
Starting in 2019, Brazilian companies will have to recognize in the balance sheet not only the financial leases, but also the operating leases. This requirement arises from the entry into force of IFRS 16. Therefore, this research seeks to identify the effects of the adoption of IFRS 16 on the performance indicators of tenant entities in the year 2018 to predict their behavior for the year 2019 when the standard will take effect. Even though several studies have been written in order to understand the effect of this norm on the main financial indicators, this work brings an updated view on 2018 financial statements. According to this standard, a lease is a contract that gives the lessee the right to use the asset for a certain period. However, recognition of the right of use and its underlying responsibility in the balance sheet will to change the reading and interpretation of ratios and the way in which we evaluate the performance of the companies. For this purpose, a sample of 40 publicly retail traded companies with the publication of the financial statements on the Brazilian stock exchange B3 and others Europeans stocks exchange were studied. The values corresponding to the operating leases were identified as well the treatment given by audit firms in the financial statement of the companies identifying as a key audit matters or not. A comparison was made between the indicator indebtedness versus EBITDA and on the indicator debt versus equity looking for changes before and after the norm into force. The result of the research identified an amount of 58 billions of dollars related to operating lease contracts not included in the balance sheets of the companies analyzed and it was verified that there will be a significant change in the indicators indebtedness of the lessees. In addition, there will be a significant increase of EBITDA of the companies once that all leasing expenses will be booked as an amortization, that is, after the EBITDA.